Global inflation - Matteo Ciccarelli; Benoît Mojon (European Central Bank (ECB), 2005)
This paper shows that inflation in industrialized countries is largely a global phenomenon. First, inflations of (22) OECD countries have a common factor that alone account for nearly 70% of their variance. This large variance share that is associated to Global Inflation is not only due to the trend components of inflation (up from 1960 to 1980 and down thereafter) but also to fluctuations at business cycle frequencies. Second, Global Inflation is, consistently with standard models of inflation, a function of real developments at short horizons and monetary developments at longer horizons. Third, there is a very robust "error correction mechanism" that brings national inflation rates back to Global Inflation. This model consistently beats the previous benchmarks used to forecast inflation 1 to 8 quarters ahead across samples and ountries.
Keywords: E31; E37; F42; 330; common factor; inflation; international business cycle; OECD countries; Inflation; Inflationskonvergenz; Inflationskonvergenz; Globalisierung; OECD-Staaten